1994
DOI: 10.2307/1940886
|View full text |Cite
|
Sign up to set email alerts
|

Costs of Inducible Defense: Protein Limitation, Growth, and Detoxification in Parsnip Webworms

Abstract: Although xanthotoxin, a linear furanocoumarin, is toxic to a wide variety of lepidopterans, the parsnip webworm, Depressaria pastinacella (Lepidoptera: Oecophoridae), is restricted to feeding on only two genera of Apiaceae, both of which contain large quantities of this toxin. The cost of cytochrome P450—mediated detoxification of xanthotoxin by this oligophagous species was examined in two artificial diet experiments. In the first experiment, growth rates, silkspinning rates, and detoxification capacity of la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 24 publications
1
61
0
Order By: Relevance
“…A similar result, reduced growth and ECD with no e ects on consumption and digestibility, was obtained by Lincoln et al (1982) when they incorporated plant resins into arti®cial diets of a given protein composition and fed them to caterpillars of Euphydryas chalcedona (Lepidoptera, Nymphalidae). Berenbaum and Zangerl (1994) also found good evidence for the hypothesis that detoxi®cation of the furanocoumarin xanthotoxin imposes a metabolic load on the parsnip webworm, Depressaria pastinacella (Lepidoptera, Oecophoridae). However, Neal (1987) was unable to ®nd metabolic costs of mixed-function oxidase induction, which is a metabolic system responsible for most detoxi®cation processes.…”
Section: Alpinamentioning
confidence: 75%
“…A similar result, reduced growth and ECD with no e ects on consumption and digestibility, was obtained by Lincoln et al (1982) when they incorporated plant resins into arti®cial diets of a given protein composition and fed them to caterpillars of Euphydryas chalcedona (Lepidoptera, Nymphalidae). Berenbaum and Zangerl (1994) also found good evidence for the hypothesis that detoxi®cation of the furanocoumarin xanthotoxin imposes a metabolic load on the parsnip webworm, Depressaria pastinacella (Lepidoptera, Oecophoridae). However, Neal (1987) was unable to ®nd metabolic costs of mixed-function oxidase induction, which is a metabolic system responsible for most detoxi®cation processes.…”
Section: Alpinamentioning
confidence: 75%
“…Appel and Martin (Appel and Martin, 1992) found that Manduca sexta (Lepidoptera) changed neither metabolic rate nor growth variables when it was fed on artificial diets with different concentrations of nicotine. Finally, Berenbaum and Zangerl demonstrated that xanthotoxin induced the expression of detoxification systems in Depressaria pastinacella (Lepidoptera) but did not affect its growth parameters (Berenbaum and Zangerl, 1994). On the other hand, Cresswell et al reported that an artificial diet containing nicotine produced an increase in metabolic rate and a reduction of net growth efficiency in larvae of Spodoptera eridania (Lepidoptera) (Cresswell et al, 1992).…”
Section: Energetic Demand Of Detoxification Systemsmentioning
confidence: 99%
“…Specifically, dietary nicotine (0.5%), a substrate of the polysubstrate monooxygenase detoxification system, was found to have significant negative effects on the weight of food ingested, weight gained, relative growth rate and conversion efficiency of digested food by S. eridania larvae on a nutrient-rich artificial diet. Furthermore, in Berenbaum et al (1994), it was shown that the detoxification of the plant allelochemical xanthotoxin was maintained, at the expense of growth, in the parsnip webworm (Depressaria pastinacella) fed nutrient deficient diets.…”
Section: Energetic Costs and Detoxificationmentioning
confidence: 99%